Organizational resilience and strategic agility: An integrative framework based on evidence during COVID-19 - Ben Arfi, Wissal; Cherbib, Jihène (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2025)
This article explores how strategic agility enables organizations to identify potential threats, mitigate risks and benefit from emerging opportunities to enhance their resilience during a crisis. Based on a qualitative study conducted from April 2020 to March 2021 among 11 French companies, the results highlight how strategic agility can be a catalyst for achieving organizational resilience. This study presents a structured three-phase process to help organizations navigate and adapt to disruptive events. Phase 1 focuses on winning back customers and leveraging digital tools to improve loyalty and efficiency. Phase 2 focuses on strengthening team cohesion and reconfiguring processes to foster collaboration and streamline operations. Phase 3 involves rethinking strategic activities and renewing business models to ensure adaptability and long-term growth.